Moral Learning Based on Teacher Exemplars as a Strategy for Strengthening Islamic Character Education - Ahmad Wahyu Hidayat (JISEI: Journal of Islamic Studies and Educational Innovation, 2025)
Moral degradation among students has become a significant challenge in contemporary education, particularly in the context of globalization and rapid socio-cultural change. Islamic character education is expected to provide moral guidance; however, its implementation often remains cognitive-oriented and lacks effective internalization. This study aims to analyze moral learning based on teacher exemplars as a strategic approach to strengthening Islamic character education. Using a qualitative descriptive approach, the research explores how teachers’ attitudes, behaviors, and daily interactions function as living moral models for students. Data were collected through observations, in-depth interviews, and documentation in Islamic educational institutions. The findings indicate that teacher exemplars play a central role in shaping students’ Islamic character, including honesty, discipline, responsibility, tolerance, and spiritual awareness. Moral learning grounded in exemplary behavior is more effective than purely instructional methods, as it fosters moral internalization through habituation and emotional bonding. Teachers who consistently demonstrate Islamic values in both instructional and non-instructional settings significantly influence students’ moral development. This study concludes that strengthening Islamic character education requires positioning teachers not only as knowledge transmitters but also as moral role models whose exemplary conduct becomes the core of moral learning strategies.